Delay analysis of randomised algorithms for link scheduling in wireless networks. (22nd May 2013) - Ghiasian, Ali; Saidi, Hossein; Behdadfar, Mohammad
To design a link scheduling algorithm that can maximise the throughput region yet meet the average delay constraint is a challenging issue in wireless networks. In this paper we aim to analyse and improve the delay performance of the well–studied randomised link scheduling algorithms. To this end, we first introduce a novel concept, the average hitting time, and analyse its impact on the upper bound of the average delay. We analytically show that for two given randomised algorithms achieving the same throughput region, the one with a smaller average hitting time has less average delay bound. We also show that by assigning traffic priorities in some specific applications, the achievable throughput region delivered by the randomised algorithm remains intact. This result is much valuable in the design of algorithms for some real–time applications by prioritising the traffic to reduce the average delay of those applications. The simulation results are consistent with our theoretical analysis.